TWO-SCALE NUMERICAL SIMULATION OF PROGRESSIVE TENSILE FAILURE OF HYBRID COMPOSITES - XING Chen; ZHOU ChuWei; SUN YuLin (Jixie qiangdu)
Two 3D finite element approaches for unidirectional hybrid composites were built to represent failure process in scales of individual fiber and fiber tow,respectively. The first scale approach was defined as iso-type fibers and epoxy composed fiber tow in which micro damages concerned including failures of individual fiber,matrix and fiber / matrix interface. The second scale approach assembled with different type fiber tows. In this scale,failure regularities of tow and interface between adjacent tows were considered and the former was obtained from first scale model. Cohesive zone model was used to simulate the damage and failure of component materials,this method could reflect the distribution and propagation of the crack in composites. Explicit FEM was used for both the two scale models to characterize the impaction of energy released from the broken fiber or tow. Weibull type distribution was used to describe strengths of fiber and fiber tow in the two scale approaches for charactering the randomness of failures. The two scale approaches were employed to simulate the progressive failure of carbon / glass fiber hybrid unidirectional composites under tensile load. Two distribution patterns of carbon tow in hybrid composites,i. e. coaxial and dispersed were taken into account,meanwhile for each pattern different volume ratio of carbon fiber and glass fiber was considered. The study reveals that when volume fraction of carbon tows is equal or less than 10% the second damage phenomenon is obvious,meanwhile the critical elongation and strength for coaxial hybrid composited are slightly bigger than those for dispersed one. Otherwise,the two patterns hybrid composites behave in brittle way and little discrepancy between their strengths has been found.